Strengthening the Umama Brand Promotion Strategy on the Decision to Purchase Instant Hijab Products among Students in the Sidoarjo Region: Penguatan Strategi Promosi Brand Umama Terhadap Keputusan Pembelian Produk Hijab Instan pada Kalangan Mahasiswa di Wilayah Sidoarjo - Millenia, Arum; Sukmono, Rita Ambarwati (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to find out how to strengthen the promotion strategy of the Umama instant hijab brand on purchasing decisions among students in the Sidoarjo area. This study examines respondents, namely students in the Sidoarjo area who have known and used Umama's instant hijab products in their daily lives. The method used is quantitative research with a sample of 100 students. Data collection at the interval level was carried out by distributing questionnaires. The data analysis used is the outer model test and the inner model test on the Smart PLS software application. The results of this study indicate that strengthening the promotion strategy has a positive and significant effect on purchasing decisions.